Low cadence interval training at moderate intensity does not improve cycling performance in highly trained veteran cyclists - Kristoffersen, Morten; Gundersen, Hilde; Leirdal, Stig; Iversen, Vegard V. (Frontiers in Physiology, 2014)
Purpose: The aim of the present study was to investigate effects of low cadence training at moderate intensity on aerobic capacity, cycling performance, gross efficiency, freely chosen cadence and leg strength in veteran cyclists. Method: Twenty-two well trained veteran cyclists (age: 47 ±6 years, maximal oxygen consumption (VO2max): 57.9 ±3.7 ml. kg-1. min-1) were randomized into two groups, a low cadence training group and a freely chose cadence training group. Respiratory variables, power output, cadence and leg strength were tested before and after a 12 weeks training intervention period. The low cadence training group performed 12 weeks of moderate (73-82 % of maximal heart rate (HRmax)) interval training (5 x 6 min) with a cadence of 40 revolutions per minute (rpm) two times a week, in addition to their usual training. The freely chosen cadence group added 90 minutes of training at freely chosen cadence at moderate intensity. Results: No significant effects of the low cadence training on aerobic capacity, cycling performance, power output, cadence, gross efficiency or leg strength was found. The freely chosen cadence group significantly improved both VO2max (58.9±2.4 vs. 62.2±3.2 ml. kg-1. min-1), VO2 consumption at lactate threshold (49.4 ±3.8 vs. 51.8±3.5 ml. kg-1. min-1) and during the 30 min performance test (52.8±3.0 vs. 54.7±3.5 ml. kg-1. min-1), and power output at lactate threshold (284 ±47 vs. 294 ±48 W) and during the 30 min performance test (284±42 vs. 297±50 W). Conclusion: Twelve weeks of low cadence (40 rpm) interval training at moderate intensity (73-82 % of HRmax) twice a week does not improve aerobic capacity, cycling performance or leg strength in highly trained veteran cyclists. However, adding training at same intensity (% of HRmax) and duration (90 minutes weekly) at freely chosen cadence seems beneficial for performance and physiological adaptations.